Enhanced long-lived dark photon signals at lifetime frontier detectors - Ming xuan Du (American Physical Society, 2022)
Long-lived particles that are present in many new physics models beyond the standard model, can be searched for in a number of newly proposed lifetime frontier experiments at the LHC. The signals of the long-lived dark photons can be significantly enhanced in a new dark photon model in which dark photons are copiously produced in the hidden radiation process. We investigate the capability of various lifetime frontier detectors in probing the parameter space of this model, including the far forward detectors FACET and FASER, the far transverse detector MATHUSLA, and the precision timing detector CMS-MTD.